Breeding of the Spot-billed Toucanet (Selenidera maculirostris) in the Wild - Guaraldo, Andre de Camargo [UNESP]; Staggemeier, Vanessa Graziele [UNESP] (Wilson Ornithological Soc, 2009)
The Spot-billed Toucanet (Selenidera maculirostris) is an endemic member of the Ramphastidae occurring in the Atlantic Forest in Brazil. There is anecdotal literature about this species breeding in the wild, but no data are available about parental behavior and nest morphometry. We describe observations of parental behavior of the Spot-billed Toucanet including measurements of one nest in Ilha do Cardoso State Park, São Paulo, Brazil. The nest was inside a hollow of a Lauraceae tree with the entrance hidden by leaves of Aechmea sp. (Bromeliaceae). The Spot-billed Toucanet, based on our observations and review of the literature, nests in tree cavities between 2 and 7 to above ground and both parents provision the nestlings. Received 13 July 2008. Accepted 7 June 2009.